2014
DOI: 10.1111/ijd.12365
|View full text |Cite
|
Sign up to set email alerts
|

Acitretin in psoriasis: an evolving scenario

Abstract: Acitretin, an active metabolite of etretinate, is the most widely used systemic retinoid in the treatment of psoriasis. There are several unique characteristics of this drug, which set it apart from other options in the therapeutic armamentarium of psoriasis. It is highly efficacious as monotherapy in some specific clinical subtypes of psoriasis. It has dose-sparing effects when used as combination therapy with conventional systemic drugs as well as the biologics. It is a good option for long-term maintenance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 91 publications
0
44
0
1
Order By: Relevance
“…The original retinoid mechanism was the antiproliferative effects and promotion of epithelial differentiation. Both effectively inhibit the hyperproliferation of keratinocytes and alter the abnormal differentiation seen in psoriasis [6]. However, studies have shown that a paradox exists in psoriatic lesions-there is a higher level of retinoic acid within lesions due to an alteration in vitamin A metabolism, yet retinoid therapy is effective in such lesions.…”
Section: Vitamin Amentioning
confidence: 99%
“…The original retinoid mechanism was the antiproliferative effects and promotion of epithelial differentiation. Both effectively inhibit the hyperproliferation of keratinocytes and alter the abnormal differentiation seen in psoriasis [6]. However, studies have shown that a paradox exists in psoriatic lesions-there is a higher level of retinoic acid within lesions due to an alteration in vitamin A metabolism, yet retinoid therapy is effective in such lesions.…”
Section: Vitamin Amentioning
confidence: 99%
“…Acitretin, the active acid metabolite of etretinate, is hypothesized to treat psoriasis through antiproliferative effects on keratinocytes, immunomodulatory effects, and antiangiogenic effects by binding to nuclear retinoic acid receptors and/or retinoid X receptors. 50 Unlike other systemic treatments for psoriasis, retinoids are not found to be immunosuppressive, a distinct advantage for certain patients. Acitretin generally is started at low doses (10-25 mg/d), and increased as tolerated, except in the case of generalized pustular psoriasis, where it should be started high and titrated down to the lowest effective dose.…”
Section: Acitretinmentioning
confidence: 99%
“…Acitretin generally is started at low doses (10-25 mg/d), and increased as tolerated, except in the case of generalized pustular psoriasis, where it should be started high and titrated down to the lowest effective dose. 50 A study of subjects treated with 50 mg daily of acitretin over 8 weeks reported 23% achieving PASI 75. 51 In another study, after 12 weeks of treatment with acitretin, the mean PASI improvement was 70% to 75%.…”
Section: Acitretinmentioning
confidence: 99%
See 2 more Smart Citations